Silver stress differentially affects growth of phototrophic and heterotrophic chrysomonad flagellate populations. (January 2019) - Bock, Christina; Zimmermann, Sonja; Beisser, Daniela; Dinglinger, Sarah-Maria; Engelskirchen, Simone; Giesemann, Philipp; Klink, Saskia; Olefeld, Jana Laura; Rahmann, Sven; Vos, Matthijs; Boenigk, Jens; Sures, Bernd
Abstract: Silver ions are among the predominant anthropogenic introduced pollutants in aquatic systems. As silver has effects on species at all trophic levels the community composition in aquatic habitats can be changed as a result of silver stress. The response of planktonic protists to environmental stressors is particularly important as they act both as producers and consumers in complex planktonic communities. Chrysomonad flagellates are of major interest, since this group includes heterotrophic, mixotrophic and phototrophic taxa, and therefore allows analysis of silver stress in organisms with contrasting nutritional strategies independent of a potential taxonomic bias. In a series of lab experiments, we compared the response of different trophic chrysophyte strains to low (5 μg L −1 ), medium (10 μg L −1 ) and high (20 μg L −1 ) nominal Ag concentrations in combination with changes in temperature and light intensity (phototrophs), temperature and food concentration (heterotrophs), or a combination of the above settings (mixotrophs). All tested strains were negatively affected by silver in their growth rates. The phototrophic strains reacted strongly to silver stress, whereas light intensity and temperature had only minor effects on growth rates. For heterotrophic strains, high food concentration toned down the effect of silver, whereas temperatures outside the growth optimum had a combined stress effect. The mixotrophic strains reacted differently depending on whether their nutritional mode was dominated by heterotrophy or by phototrophy. The precise response pattern across all variables was uniquely different for every single species we tested. The present work contributes to a deeper understanding of the effects of environmental stressors on complex planktonic communities. It indicates that silver will negatively impact planktonic communities and may create shifts in their composition and functioning. Graphical abstract: Image 1 Highlights: Silver affects chrysomonad growth rates depending on the mode of nutrition. High food concentrations can tone down the effect of silver in heterotrophics. Light and temperature influence the effect of silver in phototrophics only slightly. Mixotrophics react to silver depending on their predominant nutritional mode. Abstract : Silver ions affect growth rates of flagellate populations depending on their mode of nutrition and thus may cause shifts in the composition and functioning of planktonic communities.